2016
DOI: 10.1039/c6ra11038j
|View full text |Cite|
|
Sign up to set email alerts
|

Dielectric properties of pyridine–ethanol mixtures: density functional theory and experiments

Abstract: The schematic of the experimental system.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…Malloum also investigated other molecular clusters [254–256]. Huang found that the real and imaginary part of the effective permittivities of the pyridine (C 5 H 5 N)–ethanol (C 2 H 5 OH) mixture are larger than those of their pure components at some concentrations [257]. Calculations on the GMs of (C 5 H 5 N) n (C 2 H 5 OH) m ( n = 0 − 4, m = 0 − 6) suggested that this difference is related to the dipole moments of the mixture.…”
Section: Applicationsmentioning
confidence: 99%
“…Malloum also investigated other molecular clusters [254–256]. Huang found that the real and imaginary part of the effective permittivities of the pyridine (C 5 H 5 N)–ethanol (C 2 H 5 OH) mixture are larger than those of their pure components at some concentrations [257]. Calculations on the GMs of (C 5 H 5 N) n (C 2 H 5 OH) m ( n = 0 − 4, m = 0 − 6) suggested that this difference is related to the dipole moments of the mixture.…”
Section: Applicationsmentioning
confidence: 99%
“…We adapted the algorithm for chemical problems and wrapped it in a program called ABCluster. , Since then, ABCluster has gained wide applications in chemical problems from different fields. One example is that ABCluster was used to search the GMs of lanthanide (Ln) doped silicon cluster anions as large as LnSi 20 – , and the calculated photoelectron spectroscopy from these GMs agrees well with the experimental ones. Another example is that several authors searched the GMs of clusters consisting of atmosphere related molecules like water, ammonia, nitric acid, hydroxymethanesulfonic acid, sulfuric anhydride, and pentoxide–iodic acid. Using GMs of different sizes, atmospheric cluster dynamics equations can be solved, and a number of atmospheric chemical phenomena were successfully explained. ABCluster was also applied in catalysis, , materials science, solution chemistry, etc. Therefore, the ABC algorithm is proven to be a highly successful method for searching GMs of atomic and molecular clusters to solve realistic chemical problems.…”
Section: Introductionmentioning
confidence: 98%
“…[58][59][60][61][62][63][64][65][66][67][68][69][70] Using GMs of different sizes, atmospheric cluster dynamics equations can be solved 71 and a lot of atmospheric chemical phenomena were successfully explained. [58][59][60][61][62][63][64][65][66][67][68][69][70] ABCluster was also applied in catalysis, 4,[72][73][74] material science, [75][76][77] solution chemistry, [78][79][80] etc. Therefore, the ABC algorithm is proven to be a highly successful method for searching GMs of atomic and molecular clusters to solve realistic chemical problems.…”
Section: Introductionmentioning
confidence: 99%
“…One can also observe that the estimation of dielectric properties of single reagent is better than that of reagent mixtures. Researchers reported that the conventional mixture formulas cannot describe the dielectric property of mixed reagents appropriately, since the mixture may present an anomaly in its dielectric property [ 38 , 39 ]. There may be also an anomaly in the mixtures measured in the paper, causing the difference between the measured and calculated data of mixtures.…”
Section: Measured Results and Discussionmentioning
confidence: 99%